Risk of fall in patients with chronic kidney disease: results from the China health and retirement longitudinal study (CHARLS) - Pinli Lin; Biyu Wan; Jintao Zhong; Mengya Wang; Fang Tang; Lingzhen Wang; Junjun Guo; Yuling Ye; Xusheng Liu; Lu Peng; Lili Deng (BMC, 2024)
Abstract Background Chronic kidney disease (CKD), often coexisting with various systemic disorders, may increase the risk of falls. Our study aimed to assess the prevalence and risk of falls among patients with CKD in China. Methods We included patients with/without CKD from China Health and Retirement Longitudinal Study (CHARLS). Our primary outcome was the occurrence of fall accidents within the past 2 years. To enhance the robustness of our findings, we employed a multivariable logistic regression model, conducted propensity score analysis, and applied an inverse probability-weighting model. Results A total of 12,658 participants were included, the prevalence of fall accident rates were 17.1% (2,028/11,837) among participants without CKD and 24.7% (203/821) among those with CKD. In the inverse probability-weighting model, participants with CKD exhibited higher fall accident rates (OR = 1.28, 95% CI: 1.08-1.53, p = 0.005 ). Sensitivity and subgroup analysis showed the results still stable. Conclusions The population in China afflicted with CKD has a significantly heightened risk of experiencing falls, underscoring the crucial importance of intensifying efforts in assessing and preventing fall risks.